An E-Module of Math Based on Problem-Based Learning for the Subject of Fractions in Elementary School - Alfi Chasanah; Meita Fitrianawati (The Indonesian Institute of Science and Technology Research, 2023)
The purpose of the study was to create an electronic module utilizing problem-based learning strategies to aid students in comprehending fractions. The development phase employed the ADDIE model, which involves analysis, design, development, implementation, and evaluation. The research focused on evaluating the e-module's implementation and effectiveness by conducting assessments from media, subject matter, and learning experts, as well as from teachers and students. The feedback indicated that the e-module was highly feasible, with experts rating it as